Low loss waveguide-based Butler matrix with iris coupling control method for millimeterwave applications - W. Almeshehe, Muataz; Murad, Noor Asniza; A. Rahim, Mohamad Kamal; Ayop, Osman; Zubir, Farid; Abd. Aziz, Mohamad Zoinol A.; Osman, Mohamed N.; A. Majid, H. (Taylor & Francis, 2021)
This paper proposes a low loss 4×4 Butler matrix based on rectangular waveguide cavity resonators technology for millimeterwave beamforming network using iris coupling method. This method has the advantage of controlling the electrical fields and the coupling factor inside a complex medium such as waveguide cavity resonators. The coupling factor of 6 dB for 4×4 Butler matrix is achieved by tuning the iris coupling k-value between the waveguide cavity resonators. Thus, avoiding a higher phase difference losses and component losses at upper millimeterwave bands. To validate the proposed method, CST software simulations are performed under several iris coupling k-values to achieve a 6 dB coupling factor. Then, the proposed 4×4 Butler matrix is 3D metal printed using selective laser melting (SLM) technique. The measured reflection and isolation coefficients are observed below −10 dB, with coupling coefficients ranging between −6 and −7 dB. The phase differences of −42.02°, 42.02°, −130.95°, and 133.3° are achieved at the outputs. It confirmed that using this proposed method has the superiority over the conventional microstrip and waveguide coupling methods by a 1 dB coupling factor loss and a 3° phase difference error.